2019
DOI: 10.1063/1.5058733
|View full text |Cite
|
Sign up to set email alerts
|

Influence of deeply trapped energetic ions on tearing modes

Abstract: The effects of deeply trapped energetic ions (DTEIs) on the stability of tearing modes through stability criterion Δ′ are studied. In contrast to the stabilizing adiabatic effect of background plasma pressure, the adiabatic contribution of the DTEI destabilizes due to the direct coupling between the bad curvature and asymmetrical pressure of energetic ions. When the orbit width is much larger than the island width, the nonadiabatic effect of the DTEI stabilizes, which counteracts the major destabilizing adiaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The effect of energetic particles on magnetohydrodynamic (MHD) modes has become an intensive field of research for several years [1][2][3][4][5][6][7]. It was found that sometimes energetic particles (EPs) [8][9][10][11] are capable of improving MHD stability [12] in the plasma [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of energetic particles on magnetohydrodynamic (MHD) modes has become an intensive field of research for several years [1][2][3][4][5][6][7]. It was found that sometimes energetic particles (EPs) [8][9][10][11] are capable of improving MHD stability [12] in the plasma [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, a small perturbation of the magnetic field or electric field can interact with energetic particles and lead to a significant particle loss, which will damage the first wall of tokamak and even lead the plasma to extinguish. In recent years, many pioneering works on energetic particles have been made [10][11][12][13][14][15][16][17][18]. In future reactors, such as ITER and CFETR, the alpha particle heating will act as the primary heating source.…”
Section: Introductionmentioning
confidence: 99%
“…This explosive burst can lead to a fast driven nonlinear reconnection between both rational surfaces and thus can trigger off-axis sawteeth observed in RMS tokamak plasmas. [51,54] In the early nonlinear phase, the magnetic islands on both rational surfaces continue to grow and drive each other. When the magnetic separatrices of the magnetic islands on both rational surfaces merge together, the field lines of magnetic islands reconnect with the equilibrium field lines.…”
Section: The Intermediate ∆ Rs Casementioning
confidence: 99%
“…[8,32,50] The process is regarded as a new type of secondary instability by the width and the angle rating of triangularization. [51] It is noted that due to the flattening of the pressure profile in the magnetic island, the fraction of the local bootstrap current decreases, triggering the neo-classical double-tearing mode (NDTM) instability in RMS, which is different from the positive magnetic shear. In fact, a preliminary study on NDTM had been conducted by Yu et al and they found that the effects of bootstrap current on the inner rational surface and outer rational surface were quite different.…”
Section: Introductionmentioning
confidence: 99%